THE PRECAUTIONARY PRINCIPLE IN INTERNATIONAL ENVIRONMENTAL LAW AND INTERNATIONAL JURISPRUDENCE - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
This paper analysis international regulation of the precautionary principle as one of environmental principles. This principle envisages that when there are threats of serious and irreparable harm, as a consequence of certain economic activity, the lack of scientific evidence and full certainty cannot be used as a reason for postponing efficient measures for preventing environmental harm. From economic point of view, the application of precautionary principle is problematic, because it creates larger responsibility for those who create possible risks, comparing to the previous period. The precautionary principle can be found in numerous international treaties in this field, which regulate it in a very similar manner. There is no consensus in doctrine whether this principle has reached the level of international customary law, because it was interpreted differently and it was not accepted by large number of countries in their national legislations. It represents a developing concept which is consisted of changing positions on adequate roles of science, economy, politics and law in the field of environmental protection. This principle has been discussed in several cases before International Court of Justice and International Tribunal for the Law of the Sea.